2013
DOI: 10.1088/0026-1394/50/3/243
|View full text |Cite
|
Sign up to set email alerts
|

A finite element analysis of surface-stress effects on measurement of the Si lattice parameter

Abstract: A stress exists in solid surfaces even if the underlying bulk material is stress-free. This paper investigates the effect of surface stress on the value of the Si lattice parameter measured by combined x-ray and optical interferometry. An elastic-film model has been used to provide a surface load in a finite element model on the x-ray interferometer crystal. Eventually, an interferometer design is proposed to determine a measurement where the effect of the surface stress is deemed to be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 25 publications
(39 reference statements)
2
29
0
Order By: Relevance
“…In addition, a native oxide layer grows of the slab surfaces -which is expected from 1 nm to 2 nm thick, but nothing is known about its stoichiometry [21,22,23]. [13]. The red shaded area shows the interval of the stress values given in the literature [13], which ranges from −0.68 N/m to 0.76 N/m.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, a native oxide layer grows of the slab surfaces -which is expected from 1 nm to 2 nm thick, but nothing is known about its stoichiometry [21,22,23]. [13]. The red shaded area shows the interval of the stress values given in the literature [13], which ranges from −0.68 N/m to 0.76 N/m.…”
Section: Resultsmentioning
confidence: 99%
“…[13]. The red shaded area shows the interval of the stress values given in the literature [13], which ranges from −0.68 N/m to 0.76 N/m. In order to investigate the intrinsic surface stress of the oxidized (110) surface, we started by considering the pristine (110) surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These investigations did not prove that surface stresses due to oxidation, relaxation and reconstruction did not affect the lattice-parameter value (Kessler et al, 1999). The magnitude of this effect was estimated by a finite element analysis, where the surface stress (a fundamental property of the crystal interface with the environment) was modelled by an elastic membrane having a hypothetical 1 N m À1 tensile strength (Quagliotti et al, 2013). We also calculated the surface stress by density functional theory (Melis et al, 2016) and found a value exceeding 1 N m À1 , which potentially jeopardizes the measurement accuracy.…”
Section: Introductionmentioning
confidence: 97%